A Health Insurance Tax Credit for Uninsured Workers - Lawrence Zelenak (SAGE Publishing, 2001)
This paper describes a new system of tax credits to help low-income workers pay for health insurance. The system would be designed to subsidize health insurance coverage for workers who are currently uninsured, or who pay high premiums for nongroup insurance. Anyone age 19 or older who is not covered by Medicaid, Medicare, or employer-sponsored health insurance would be eligible for a health insurance tax credit (HITC), administered through the Internal Revenue Service. The base amount of the proposed credit would be $2,000 per year for each covered individual, but this amount would be adjusted for the individual's age and sex, according to the effect of age and sex on the cost of insurance coverage. The base amount of the credit would be reduced by $150 for every $1,000 by which a person's income exceeded 200% of the federal poverty level, thus limiting HITC eligibility to lower-income workers. To encourage participation in the credit program, most of the credit would be available through an advance payment system, with final reconciliation after year's end.